Affective temperaments and the risk of gestational diabetes mellitus. (1st March 2022) - Rezaei Ardani, Amir; Tara, Fatemeh; Hatami, Seyedeh Behnaz; Naghizadeh Kashani, Sara; Emadzadeh, Maryam; Nahidi, Mahsa
Abstract: Objective: Gestational diabetes mellitus (GDM) is the most common medical complication of pregnancy. The current study aimed to investigate the possibility of a relationship between affective temperaments and GDM. Methods: This ethically approved cross-sectional study was conducted on 120 pregnant women with impaired glucose tolerance and 120 healthy pregnant women, all of whom were admitted to hospitals affiliated with Mashhad University of Medical Sciences for delivery during 2019. Depression Anxiety Stress Scale (DASS)-21 and Temperament Evaluation of Memphis, Pisa, Paris and San Diego-auto-questionnaire (TEMPS-A) were used to gather data. Mann–Whitney test was used to compare data between the two groups. A multivariate binary logistic regression model with maternal age, body mass index, and multiparity as the covariates was used to assess factors associated with GDM. Results: Outcomes of TEMPS-A showed significantly higher scores of anxious and irritable temperaments in the GDM group compared to the control group ( p = 0.014 and 0.023, respectively). Multivariate regression showed anxious temperament to be the sole independent predictor of GDM (odds ratio = 1.09, 95%confidence interval = 1.030–1.153; p = 0.003). DASS-21 anxiety score was also significantly higher among patients with GDM ( p = 0.002). Severity of anxiety and stress according to DASS-21 was also significantly greater in patients with impaired glucose tolerance ( p < 0.001 and p = 0.016, respectively). Conclusions: It is ostensible that affective temperaments, especially anxious temperament, are potentially associated with the development of GDM and impaired glucose metabolism during pregnancy. Key points: The association of affective temperaments with pregnancy complications has drawn compelling interest. The findings of this study showed significantly higher scores of anxious and irritable temperaments in GDM patients. GDM patients also showed significantly higher levels of anxiety compared to controls. Predominance of anxious temperament can be a potential risk factor that contributes to the development of GDM. Monitoring for GDM is especially recommended in pregnant women with predominant anxious and irritable temperaments.